DESAIN PENELITIAN DALAM ANALISIS KEBIJAKAN PENDIDIKAN: PENDEKATAN, IMPLEMENTASI, DAN TANTANGANNYA - Istiqomah; Salamah; Dina Hermina (PT. Saha Kreasi Indonesia, 2026)
This study aims to analyze research design in educational policy, including its approaches, implementation, and challenges in the policy research process. The study employed a qualitative approach using a library research method by reviewing books, scientific journals, and relevant policy documents. Data were collected through documentation studies and analyzed descriptively through data reduction, data presentation, and conclusion drawing. The findings indicate that research design plays an important role in producing evidence-based educational policies that are relevant to educational needs. Three main approaches are commonly used in educational policy research, namely quantitative, qualitative, and mixed methods approaches, each of which has its own characteristics and advantages in analyzing educational policies. The implementation of research design has also been applied in various educational policy studies, such as the evaluation of School Operational Assistance (BOS), the Merdeka Curriculum, and inclusive education policies. In addition, the study found that the main challenges in educational policy research design include limited data access, stakeholder complexity, and gaps between theory and practice in the field. Therefore, a systematic and comprehensive research design is essential to support effective, adaptive, and quality-oriented educational decision-making.